A protective role for nitric oxide and salicylic acid for arsenite phytotoxicity in rice (Oryza sativa L.) - Singh, Amit Pal (Plant physiology and biochemistry : PPB, 2017)
Copyright © 2017. Published by Elsevier Masson SAS.